The theology of the books of Nahum, Habakkuk, and Zephaniah - Timmer, Daniel C. (Old Testament theology, 2024)
"The books of Nahum, Habakkuk, and Zephaniah address problems in and around ancient Judah in ways that are as incisive and critical as they are optimistic and constructive. Daniel C. Timmer's study situates these books in their social and political contexts, examining their unique theology and later cultural reception"--